Recatadas e pudorosas: O vestuário das personagens femininas espanholas como reflexo das qualidades morais da mulher no Regime de Franco (1939-1952) (Dialogos, 2023)
This research aims to analyze women's wardrobe in Spanish films made between 1939 and 1952. It is based on the premise that the Regime used movie screens as a school for behavior. This was an apparently harmless way to indoctrinate the population in prevailing principles in a divided society, fresh out of a Civil War. Films became visual proposals of what was accepted and acceptable, not only in terms of love, sex, and gender relations, but also in the way one was to dress. Cinema, controlled by censorship, contributed to instating a female dress code that defined aesthetic parameters, but also moral categories. Films establish the limits of modesty. It was also to promote a system to indicate socially correct and incorrect trajectories, based on the development of plots and the creation of stereotyped characters. The keys to social success and failure.